Exposure to Volatile Essential Oils of Myrtle (Myrtus communis L.) Leaves for Improving the Postharvest Storability of Fresh Loquat Fruits - Nadire Pelin Bahadırlı; İbrahim Kahramanoğlu; Chunpeng Wan (Journal of Food Quality)
Fresh loquat (Eriobotrya japonica Lindl.) fruits easily lose their marketability because of fungal spoilage, browning, and weight loss after harvest. The use of essential oils as postharvest treatment is a talented alternative to fungicides mainly because of their ability to reduce respiration and transpiration of the fresh fruits during storage. However, the postharvest studies with the volatiles of essential oils are limited. The present study was conducted to determine the effectiveness of volatile essential oils of myrtle (Myrtus communis L.) leaves for preserving the postharvest storability of loquat fruits. Test fruits of the present study were exposed to 5 different treatments, which are (i) water vapor (2 min), (ii) myrtle leaves (3% w/w), (iii) myrtle leaf vapor (2 min), (iv) myrtle leaf vapor (10 min), and (v) untreated control. A total of 30 compounds were isolated from the essential oil, and the three highest amounts of compounds were determined as eucalyptol (39.38%), α-pinene (24.98%), and linalool (8.18%). Exposure to myrtle leaves (3% w/w) and myrtle leaf vapor (2 min) was also noted to provide higher efficacy for reducing the weight loss, decay incidence, and browning index.